Identifying Test Cases for Stored Procedure Using Cyclomatic Complexity Approach - Rosmah, Ismail (2009)
Testing is very important but expensive and time consuming process in software development. Software quality enhancement can be achieved through the use of a systematic program testing methodology. Few testing methodologies were discussed in this paper such as cyclomatic complexity, specification-based testing, and structural-based automatic program testing. This paper complements a research on cyclomatic complexity approach in determining the number of test cases that are necessary to achieve thorough test coverage of a particular Oracle stored procedures. Cyclomatic complexity which was developed by Thomas J. McCabe Sr. in 1976 is used to measure the complexity of a program. It directly measures the number of linearly independent paths through a program's source code. The goal of this study is to identify the minimum number of test cases required or a given stored procedure, and cyclomatic complexity was chosen as an approach to achieve this goal. It was discussed thoroughly in chapter 3 of this paper, and testing of this approach was explained in chapter 4. It was found that the higher cyclomatic complexity measure indicates the higher complexity of a program and is more complex to maintain.